Opinion Dynamics and Wisdom under Conformity - Berno Buechel; Tim Hellmann; Stefan Kölßner (Fondazione Eni Enrico Mattei (FEEM), 2014)
We study a dynamic model of opinion formation in social networks. In our model, boundedly rational agents update opinions by averaging over their neighbors' expressed opinions, but may misrepresent their own opinion by conforming or counter-conforming with their neighbors. We show that an agent's social influence on the long-run group opinion is increasing in network centrality and decreasing in conformity. Concerning efficiency of information aggregation or "wisdom" of the society, it turns out that misrepresentation of opinions need not undermine wisdom, but may even enhance it. Given the network, we provide the optimal distribution of conformity levels in the society and show which agents should be more conforming in order to increase wisdom.
Keywords: C72; D83; D85; Z13; 330; Opinion Leadership; Wisdom Of Crowds; Consensus; Social Networks; Conformity; Eigenvector Centrality